Social norms and economic incentives in firms - Steffen Huck; Dorothea Kübler; Jörgen W. Weibull (Institute for the Study of Labor (IZA), 2010)
This paper studies the interplay between economic incentives and social norms in firms. We introduce a general framework to model social norms arguing that norms stem from agents' desire for, or peer pressure towards, social efficiency. In a simple model of team production we examine the interplay of different types of contracts with social norms. We show that one and the same norm can be output-increasing, neutral, or output-decreasing depending on the incentive scheme. We also show how social norms can induce multiplicity of equilibria and how steeper economic incentives can reduce effort.
Keywords: D23; 330; social norms; incentives; contracts